Pengaruh Emotional Labor terhadap Employee Well-being pada Jurnalis - Andi Nurul Izzah Ilham; Hilwa Anwar; Rahmawati Syam (eScience Humanity Journal, 2026)
Journalist encounter various interactions with sources during news coverage, which may negatively impact their well-being if not accompanied by appropriate emotion regulation. This study aims to examine the effect of emotional labor specifically surface acting and deep acting on employee well-being among journalist. This study use simple linear regression analysis and involved 270 active journalist as respondents. This study found that deep acting has a positive and significant effect on the employee well-being of journalist (R2 = 0,058, p = 0,000 < 0,05). However, surface acting did not have a significant effect on employee well-being among journalist (p = 0,068 > 0,05).  This study provides an important contribution to understanding emotional labor, particularly deep acting, in assisting journalists to enhance their well-being.